DBS reimplantation to opposite side as a treatment for DBS-withdrawal syndrome - SÖNMEZ, ÖZCAN; ÖMERCİKOĞLU ÖZDEN, HATİCE; GÜNAL, DİLEK; BAYRAKLI, FATİH (My University, 2022)
Objectives: STN-DBS treatment has been effective on motor Parkinson’s Disease symptoms also improvement in motor symptoms ve been shown to be better than medical therapy at an earlier stage of the disease. When STN-DBS treatment is interrupted rare but lifethreatening complication occur known as DBS-withdrawal syndrome. Akinesia, rigidity, dysarthria, dysphagia, and autonomic instability seen in DBS-withdrawal syndrome and ICU setting is necessary. In the light of current knowledge, as soon as possible STN-DBS reimplantation surgery has been shown best treatment for this rare but life-threatening condition. Methods: 33-year-old male, diagnosed with Parkinson\"s disease 10 years ago and started to take bilateral STN-DBS therapy. Had two other operation both due to infected infraclavicular IPG. The cause of the frequent infection was thought to be the patient\"s scratching obsession. After 8 months of the last surgery, the patient was admitted to our clinic with purulent discharge from the IPG pocket extension but not seen any sign of infection. UPDRS-III was 63 points. IPG generator and extension were cut below the connection between lead and IPG cables so that lead tips were preserved from surrounding tissue. After surgery, the patient developed DBS-withdrawal symptoms like akinesia, aphagia, rigidity, and dysarthria, UPDRS-III score rose to 102 points. Levadopa treatment rose to 750 mg but no improvement was seen. Another surgery was planned for the patient because clinical symptoms did not improve. In surgery former cranial and postauricular incisions were combined and reached leads. Leads were dissected from surrounding tissue, from postauricular incision to burr holes until they moved freely. After that new IPG pocket was prepared in the contralateral infraclavicular area and leads and IPG cables were connected. Results: After surgery, the system switched on, and system values and medication were rearranged. The patient’s clinal symptoms improved quickly. On the seventh day after the operation, the patient was discharged when UPDRS-III score was 72 points. Conclusions: Although a limited number of cases have been reported in the literature, we will face this medical emergency more frequently with the increasing use of STN-DBS. In our solution, this life-threatening emergency was resolved by moving the leads to the opposite side.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Health Sciences; Klinik Tıp (MED); Klinik Tıp; CERRAHİ; Clinical Medicine (MED); CLINICAL MEDICINE; SURGERY; Cerrahi; Surgery